2013
DOI: 10.1149/05051.0033ecst
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of TiO2 Microstructure and Introduction of Silver Nanoparticles on Conversion Efficiency of Sb2S3 Sensitized Semiconductor Solar Cells

Abstract: Sensitized semiconductor solar cells consisting of alternative heterojunction materials (TiO2/Sb2S3/CuSCN) are characterized by an extremely thin absorber that allows effective charge transportation due to reduction in recombination. In these cells, Sb2S3 exhibited both positive and negative effects; it generated photocarriers and protected the cell from leakage current, but also behaved as a recombination center and increased the ohmic resistance. CuSCN was the additional critical factor of a cell performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In our past study, localized surface plasmons (LSPs) of silver nanoparticles (AgNPs) were applied to Sb2S3-based ETA solar cells. The photo-absorption was improved successfully without increasing the absorber layer thickness, and JSC was significantly increased from 0.66 mA/cm 2 to 1.88 mA/cm 2 (7). In that study, evaluation of the microstructure of porous TiO2 at various porosity revealed that high porosity cells achieved an improved cell performance compared to low porosity cells.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In our past study, localized surface plasmons (LSPs) of silver nanoparticles (AgNPs) were applied to Sb2S3-based ETA solar cells. The photo-absorption was improved successfully without increasing the absorber layer thickness, and JSC was significantly increased from 0.66 mA/cm 2 to 1.88 mA/cm 2 (7). In that study, evaluation of the microstructure of porous TiO2 at various porosity revealed that high porosity cells achieved an improved cell performance compared to low porosity cells.…”
Section: Introductionmentioning
confidence: 79%
“…Influence of Sb2S3 on the performance of Sb2S3-based ETA solar cells with compact TiO2 films (flat cells) or porous TiO2 has already been discussed in our previous research. We found four different effects of Sb2S3 on the cell performance; Sb2S3 generates photo carriers and also protects the cell from leakage current, but on the other hand Sb 2 S 3 behaves as a recombination center and also increases the ohmic resistance of the cell (7).…”
Section: Introductionmentioning
confidence: 94%
“…Following the success of drop-cast deposition procedures [64,66], several reports of inkjet-printed CuSCN HTLs emerged [67][68][69]. It was shown that the morphology of the inkjet-printed CuSCN dependents on deposition temperature and the properties of the ink, and hence, device performance varies accordingly.…”
Section: Printing Methodsmentioning
confidence: 99%
“…In addition to its electronic properties, CuSCN also has exceptionally versatile processing properties. Various solution-processing methods can be utilized to deposit CuSCN at low temperatures, including spin-coating, 11 , 20 , 25 ink-jet printing, 26 , 27 doctor blading, 28 , 29 and electrochemical deposition. 30 32 These advantages enable the growth of CuSCN films with thicknesses in the range from 10 to several 100 s of nanometers, which facilitates the application of CuSCN in p-channel thin-film transistors (p-TFTs).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its electronic properties, CuSCN also has exceptionally versatile processing properties. Various solution-processing methods can be utilized to deposit CuSCN at low temperatures, including spin-coating, ,, ink-jet printing, , doctor blading, , and electrochemical deposition. These advantages enable the growth of CuSCN films with thicknesses in the range from 10 to several 100 s of nanometers, which facilitates the application of CuSCN in p-channel thin-film transistors (p-TFTs). , Solvents, such as diethyl sulfide (DES) and dipropyl sulfide, are commonly used to dissolve CuSCN. Due to the inert, stable, and noncorrosive nature of these solvents, the resulting solutions do not damage commonly used substrate materials such as SiO 2 , Al 2 O 3 , and indium tin oxide, during solution processing.…”
Section: Introductionmentioning
confidence: 99%